THE IMPLEMENTATION OF THE STATE FAMILY POLICY IN MODERN RUSSIA - S. Kuzin; O. Kuchmaeva (Вестник университета)
Аnnotation: The smooth running of the modern family is impossible without implementation of the state family policy. Family policy is aimed not only to support individual families, but also to assist the social institution of the family is a vital necessity. From the impact of family policy depends on the decision of all without an exception of problems - from security, to solve the problem of population reproduction, to the formation of human capital in ensuring the competitiveness of the economy and, ultimately, problem solving, historical survival. The achievement of high standards and quality of life of Russian citizens is impossible without taking into account the interests of the family as the basic unit of society.